Left juxtaposition of the auricles with l-position of the aorta. Report of 6 cases. Issue 3 (March 1977) - Allwork, S P; Urban, A E; Anderson, R H
Abstract : Six hearts are described in which juxtaposition of the auricles to the left of the great arteries (left juxtaposition) was associated with l-postion of the aorta. Atrial anatomy was abnormal but constant; the os of the right auricle occupied the expected site of the atrial septum, producing posterior and inferior desplacement of this structure. This is of importance since the os could be mistaken for a defect of the atrial septum, while the displacement of actual defects is of significance to any intended catheterisation procedure including atrial septostomy. Five of the hearts showed atrioventricular concordance while the other specimen was an example of primitive ventricle with a right-sided outlet chamber. The ventriculoarterial connection in this latter case was normal, with l-malposition (anatomically corrected malposition). Ventriculoarterial connections in the other hearts were transposition in 3, single aortic trunk with pulmonary atresia in 1, and an intermediate between double outlet right ventricle and transposition in the other. These cases confirm the observation that juxtaposition of the auricles is associated with severe cyanotic congenital heart disease.